2020
DOI: 10.33393/grhta.2020.2027
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness and budget impact of a lifestyle intervention to improve cardiometabolic health in patients with severe mental illness

Abstract: Methods: Patients (n = 244) were randomized to receive either care-as-usual or a lifestyle intervention in which mental health nurses coached patients in changing their lifestyle by using a web tool. Costs and quality of life were assessed at baseline and at 6 and 12 months. Incremental costs per centimeter waist circumference (WC) lost and per Quality-Adjusted Life Year (QALY) gained were assessed. Budget impact was estimated based on three intervention-uptake scenarios using a societal and a third-party paye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…This is also in line with the publications of the STRIDE study (90). Moreover, a Dutch lifestyle study performed in a similar setting as the SMILE study (the LION study), also reported that some clients may need more support than others (82). This emphasizes and confirms the importance of tailoring a lifestyle intervention in this diverse population (90,93).…”
Section: Methodssupporting
confidence: 84%
See 4 more Smart Citations
“…This is also in line with the publications of the STRIDE study (90). Moreover, a Dutch lifestyle study performed in a similar setting as the SMILE study (the LION study), also reported that some clients may need more support than others (82). This emphasizes and confirms the importance of tailoring a lifestyle intervention in this diverse population (90,93).…”
Section: Methodssupporting
confidence: 84%
“…Policy makers can use the information on effectiveness and cost-effectiveness in decision-making, i.e., to decide whether it is worthwhile implementing the intervention in routine practice. This is specially of value as cost-effectiveness studies in this population are currently lacking (41,191). In our study, the intervention was costeffective for the body weight change outcome (-3.8kg; 95% CI -6.30 ; -1.23), as there were lower overall costs and people in the intervention group lost more weight than in the control group.…”
Section: Methodological Considerations and Implications For Researchmentioning
confidence: 60%
See 3 more Smart Citations